Modernising vocational education and training : fourth report on vocational education and training research in Europe. Synthesis report - (:unkn) unknown (Publications Office of the European Union, 2009)
"Increasing Europe's competitiveness while preserving the European social model, coping with population ageing, reducing unemployment, tackling labour-market skill needs and shortages, and improving enterprises' economic performance all exert pressures on VET, pushing its modernisation. This fourth report on VET research in Europe analyses the above pressures for VET modernisation. Throughout this publication, Cedefop has gatherd evidence for the role VET plays in sustaining economic development, promoting active ageing, ensuring adequate skill supply, supporting corporate innovation capacity, growth and productivity, combating social exclusion and improving social cohesion." (Herausgeber, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; G 2.1 Globalisierung; G 1.2.2.4 Arbeitslosigkeit; G 1.2.3.2 Anforderungen & Bedarfe; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; G 2.4 Sozialer Wandel; P 3.2 Lehrpersonal; L 5 Beratung & Orientierung; I 2.2 Europa; Berufsbildung; Wettbewerbsfähigkeit; Wirtschaftswachstum; Humankapital; Jugendarbeitslosigkeit; Fachkräftemangel; Arbeitskräftemobilität; Demografischer Wandel; Betriebliche Berufsausbildung; Kosten-Nutzen-Relation; Ausgrenzung; Soziale Mobilität; Lernergebnisorientierung; Bildungspersonal; Lehrerausbildung; Berufsberatung; Bildungsberatung; Europa